The effectiveness of methanol extract and fractinations fromleaves of mangroveSonneratia albaand Bruguiera gymnorrhizafor the prevention of white spot syndrome virus (WSSV) infection in black tiger shrimp Penaeus monodon - Muliani, Muliani; Endang Susianingsih (Jurnal Akuakultur Indonesia)
ABSTRACT